La fin des rois? : 200 photographies et documents - Drach, Frédéric; Bainville, Jacques; Bour, Anna; Kuh, Anton; Loubès, Jean; Madol, Hans-Roger; Nicolaevsky, Boris I. (Paris : Les illustrés français, 1934)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: politieke geschiedenis; Europa